G(q) pathway regulates proximal C-type lectin-like receptor-2 (CLEC-2) signaling in platelets - Badolia, Rachit (J Biol Chem, 2017)
Platelets play a key role in the physiological hemostasis or pathological process of thrombosis. Rhodocytin, an agonist of the C-type lectin-like receptor-2 (CLEC-2), elicits powerful platelet activation signals in conjunction with Src family kinases (SFKs), spleen tyrosine kinase (Syk), and phospholipase γ2 (PLCγ2). Previous reports have shown that rhodocytin-induced platelet aggregation depends on secondary mediators such as thromboxane A2 (TxA2) and ADP, which are agonists for G-protein-coupled receptors (GPCRs) on platelets. How the secondary mediators regulate CLEC-2-mediated platelet activation in terms of signaling is not clearly defined. In this study, we report that CLEC-2-induced Syk and PLCγ2 phosphorylation is potentiated by TxA2 and that TxA2 plays a critical role in the most proximal event of CLEC-2 signaling, i.e. the CLEC-2 receptor tyrosine phosphorylation. We show that the activation of other GPCRs, such as the ADP receptors and protease-activated receptors, can also potentiate CLEC-2 signaling. By using the specific G(q) inhibitor, UBO-QIC, or G(q) knock-out murine platelets, we demonstrate that G(q) signaling, but not other G-proteins, is essential for GPCR-induced potentiation of Syk phosphorylation downstream of CLEC-2. We further elucidated the signaling downstream of G(q) and identified an important role for the PLCβ-PKCα pathway, possibly regulating activation of SFKs, which are crucial for initiation of CLEC-2 signaling. Together, these results provide evidence for novel G(q)-PLCβ-PKCα-mediated regulation of proximal CLEC-2 signaling by G(q)-coupled receptors.